Neurally Adjusted Ventilatory Assist vs. Conventional Mechanical Ventilation in Adults and Children With Acute Respiratory Failure: A Systematic Review and Meta-Analysis - Wu, Mengfan; Yuan, Xueyan; Liu, Ling; Yang, Yi (Frontiers in Medicine, 2022)
Background: Patient-ventilator asynchrony is a common problem in mechanical ventilation (MV), resulting in increased complications of MV. Despite there are some evidences for the efficacy on improving synchronization of neurally adjusted ventilatory assist (NAVA), controversy over the physiological and clinical outcomes of its still remains. Herein, we conducted a systematic review and meta-analysis to determine the relative impact of NAVA or conventional mechanical ventilation (CMV) modes on the important outcomes of adults and children with acute respiratory failure (ARF). Methods: Qualified studies were searched in PubMed, EMBASE, Medline, Web of Science, Cochrane Library and additional quality evaluations up to 5 October 2021. The primary outcome was asynchrony index (AI); secondary outcomes contained the duration of MV, intensive care unit (ICU) mortality, the incidence rate of ventilator-associated pneumonia, pH, and PaCO2. Statistical heterogeneity for the outcomes was assessed using the I2 test. Data analysis of outcomes using odds ratio (OR) for ICU mortality and ventilator-associated pneumonia incidence and mean difference (MD) for AI, duration of MV, pH, and PaCO2 with 95% confidence interval (CI) was expressed. Results: Eighteen eligible studies (n=919 patients) were eventually enrolled. For the primary outcome, NAVA may reduce AI (MD=-21.06; 95% CI -28.06 to -14.07; p<0.001). For the secondary outcomes, the duration of MV in NAVA mode was 2.64 days lower than other CMVs (MD=-2.64; 95% CI -4.88 to -0.41; P=0.02), and NAVA may decrease ICU mortality (OR=0.60; 95% CI 0.42 to 0.86; P=0.006). There was no statistically significant difference in the incidence of ventilator-associated pneumonia, pH, and PaCO2 between NAVA and other MV modes. Conclusions: Our study suggests that NAVA ameliorates synchronization of patient-ventilator, improves the important clinical outcomes of patients with ARF comparing with CMV modes.